Health-Related Quality of Life in European Childhood Cancer Survivors: Protocol for a Study Within PanCareLIFE - Calaminus, Gabriele; Baust, Katja; Berger, Claire; Byrne, Julianne; Binder, Harald; Casagranda, Leonie; Grabow, Desiree; Grootenhuis, Martha; Kaatsch, Peter; Kaiser, Melanie; Kepak, Tomas; Kepáková, Kateřina; et al. (JMIR research protocols, 2021)
BACKGROUND: Survival after childhood cancer has improved to more than 80% during the last few years, leading to an increased number of childhood cancer survivors. Cancer itself, or its treatment, may cause chronic health conditions, including somatic and mental sequelae, which may affect survivors' health-related quality of life (HRQoL). OBJECTIVE: The project PanCareLIFE aims to establish a large database with comprehensive data on childhood cancer survivors from different European countries, including data on HRQoL. Within PanCareLIFE, this study aims to describe HRQoL in survivors, investigate predictors of HRQoL, and describe the association of HRQoL with hearing and female fertility impairment. This paper describes the design of the HRQoL study, the origin of data, strategies for data collection, and sampling characteristics of survivors from each contributing country. METHODS: A total of 6 institutions from 5 European countries (the Czech Republic, France, Germany, the Netherlands, and Switzerland) provided data on HRQoL assessed with the Short Form 36 and on relevant predictors. The central PanCareLIFE data center aggregated the data and harmonized the variables between the institutions. Survivors were eligible if they received a diagnosis of cancer according to the 12 main groups of the International Classification of Childhood Cancer, 3rd edition, or Langerhans cell histiocytosis; were aged ≤18 years at the time of diagnosis; were residents of the respective country at the time of diagnosis; had survived ≥5 years after cancer diagnosis; were aged ≥18 years at the time of the questionnaire survey; and did not refuse to registration in the national or local childhood cancer cohort. RESULTS: We identified 24,993 eligible survivors. Of those, 19,268 survivors received a questionnaire and 9871 survivors participated, resulting in response rates of 9871/24,993 (39.50%) of eligible survivors and of 9871/19,268 (51.23%) invited survivors. Most participants were diagnosed with cancer between the ages of 10 and 14 years (3448/9871, 34.93%) or <5 years (3201/9871, 32.43%). The median age was 8 years. Of the 9871 participants, 3157 (31.97%) were survivors of leukemia, 2075 (21.02%) lymphoma, and 1356 (13.7%) central nervous system (CNS) tumors. Most participants (9225/9871, 93.46%) had no history of a subsequent tumor; 77.45% (7645/9871) received chemotherapy with or without other treatments. More than half (5460/9871, 55.31%) were aged 25 to 34 years at the time of the HRQoL study. Participating survivors differed from nonparticipants; participants were more often women, survivors of leukemia or lymphoma, and less frequently, survivors of CNS tumors than nonparticipants. CONCLUSIONS: PanCareLIFE successfully assessed HRQoL and its predictors in 9871 European survivors of childhood cancer. This large population will permit detailed investigations of HRQoL after childhood cancer, particularly the impact of hearing and female fertility impairment on HRQoL. INTERNATIONAL REGISTERED REPORT IDENTIFIER (IRRID): RR1-10.2196/21851.